Merle Lipton, Liberals, Marxists, and Nationalists. Competing interpretations of South African History: Not the Kraken (Historia, 2021)
As long ago as 1994, Bill Freund wrote that the "liberal-cum-radical school of South African historiography has long since achieved total victory, real hegemony". Quoting this passage with approval more than ten years later, Christopher Saunders remarked that "today no major controversy divides the historical profession in South Africa". It is a pity that no one remembered to inform Merle Lipton in time to prevent her steaming in from Jurassic Park with her new book entitled Liberals, Marxists and Nationalists. Lipton would agree that the last decade or so has seen a convergence of interpretation among South African historians, but she would insist that this is because "the neo-Marxists (who now refer to themselves as progressives or radicals)" have been forced by the weight of the evidence to adopt the "conventional liberal version ... even liberal values and policies, such as market mechanisms and 'bourgeois' political institutions" (pp 4-5). Most reprehensibly, however, the neo-Marxists are too dishonest to admit that they have lost. They persist in claiming that it is themselves who have transformed South African history, and they have even upped the volume of their hostile anti-liberal rhetoric, for example at the Truth and Reconciliation Commission.